THE SITUATION OF EDUCATORS IN THE KHARKIV REGION DURING THE HOLODOMOR OF 1932–1933: ACHIEVEMENTS, DIFFICULTIES AND PROBLEMS (HISTORIOGRAPHICAL AND SOURCE STUDIES ASPECTS) (Південний архів (історичні науки), 2022)
The aim of the work is to analyze the domestic scientific and journalistic literature devoted to the characteristics of the state of education during the Holodomor of 1932–1933 in Ukraine on the example of Kharkiv region. To achieve it, the most widely used methods are historical-comparative and hermeneutic. Results. The process of studying the state of education and the role of educators during the Holodomor of 1932–1933 in modern domestic journalistic literature is considered. It was revealed that the most thorough local lore studies on the history of the state of education during the Holodomor of 1932–1933 in the Kharkiv region belong to T. Polishchuk. Fragmentary information and mentions about the living conditions of educators of Kharkiv region in 1932–1933 were found in the local lore works of L. Isaiv, I. Skotar, V. Strilets, I. Putria and other researchers. Conclusions. The biggest problem in the study of the situation of educators in 1932–1933 in Kharkiv and Kharkiv region is that there is no historiographical aspect of thorough works that would comprehensively consider and analyze both the achievements and problems of educators. In the journalistic literature, descriptions of pictures of socio-economic life of educators often lack specifics, the facts are presented separately, some information needs further study and explanation, at least because modern realities and living standards of that time are extremely different. Modern scientific and journalistic literature reports on the obvious achievements of educators in the early 1930s: the steady increase in literacy, the law on compulsory secondary education, the expansion of the network of secondary, vocational and higher education institutions. However, no thorough work devoted to comprehensive coverage of the historiography of this issue has been found. To describe the holistic picture of the situation of educators in 1932–1933 in Kharkiv and Kharkiv region, further research requires expanding the source base of this problem, historical assessments of various researchers, as well as biographies of prominent educators and the uniqueness of their teaching methods.
Keywords: publicist literature, famine of 1932–1933, archive materials, Kharkiv region, historiography, historiographical sources